Sie sind auf Seite 1von 3

Statistics 351 Fall 2007 Midterm #1 Solutions

1. (a) By definition,

x y

fX (x) =

2e e

dy = 2e

and

Z
fY (y) =



= 2e2x , x > 0,
e

y

y
x y

2e e

dx = 2e


 y

= 2ey 1 ey ,
e

x

y > 0.

1. (b) Since fX,Y (x, y) 6= fX (x) fY (y), we immediately conclude that X and Y are not
independent random variables.
1. (c) By definition,
fY |X=x (y) =

fX,Y (x, y)
2exy
=
= exy , 0 < x < y < .
fX (x)
2e2x

1. (d) By definition,
Z

E(Y |X = x) =

y fY |X=x (y) dy =

y exy dy.

Let u = y x so that du = dy and the integral above becomes


Z
Z
Z
Z
xy
u
u
ye
dy =
(u+x)e du =
ue du+x
eu du = (2)+x(1) = 1+x
x

and so E(Y |X) = 1 + X.


1. (e) Using (d) we find E(Y ) = E(E(Y |X)) = E(1 + X) = 1 + E(X). However,
Z
Z
E(X) =
x fX (x) dx =
2xe2x dx.

Let u = 2x so that du = 2dx and the integral above becomes


Z
Z
1 u
1
1
2x
2xe
dx =
ue du = (2) = .
2 0
2
2
0
Therefore,
E(Y ) = 1 + E(X) = 1 +

1
3
= .
2
2

1. (f ) If U = X + Y and V = X, then solving for X and Y gives


and Y = U V.

X=V
The Jacobian of this transformation

x

u
J =
y

u

is

x

v 0 1
=
= 1.
y 1 1

v

Therefore, we conclude
fU,V (u, v) = fX,Y (v, u v) |J| = 2ev(uv) 1 = 2eu
provided that 0 < 2v < u < (or, equivalently, 0 < v < u2 < ). The marginal for
U is given by
Z
Z u/2
u
fU (u) =
fU,V (u, v) dv =
2eu dv = 2eu = ueu , u > 0.
2

0
We recognize this as the density of a (2, 1) random variable. That is, U = X + Y
(2, 1) as required.
2. (a) We find
E(Xn+1 |X1 , . . . , Xn ) = E(Xn Yn+1 |X1 , . . . , Xn )
= Xn E(Yn+1 |X1 , . . . , Xn ) (by taking out what is known)
= Xn E(Yn+1 ) (since Yn+1 is independent of X1 , . . . , Xn )
= Xn 1
= Xn
and so {Xn , n = 1, 2, . . .} is, in fact, a martingale.
2. (b) For n = 1, 2, . . ., we find
E(Xn ) = E(Y1 Y2 Yn ) = E(Y1 ) E(Y2 ) E(Yn ) = 1
using the fact that Y1 , Y2 , . . . are independent.
3. (a) By the law of total probability,
Z
P (X = 0) =

Z
P (X = 0|A = a)fA (a) da =

and
Z
P (X = 1) =

1
1
a2
(1 a) da = a =
2 0 2

Z
P (X = 1|A = a)fA (a) da =

1
a2
1
a da = = .
2 0 2

3. (b) By definition,
fA|X=0 (a) =

(1 a) 1
P (X = 0|A = a)fA (a)
=
= 2(1 a),
P (X = 0)
1/2

0 < a < 1,

and

P (X = 1|A = a)fA (a)


a1
=
= 2a, 0 < a < 1.
P (X = 1)
1/2

If U = 3 X + Y and V = X 3 Y , then solving for X and Y gives

3U + V
U 3V
X=
and Y =
.
4
4
fA|X=1 (a) =

4.

The Jacobian of this transformation is




x x



u v 3/4

1/4
=
= 1/4.
J =
1/4 3/4
y y


u v
Therefore, we conclude

fU,V (u, v) = fX,Y


=

1
fX
4

!
3u + v u 3v
,
|J|
4
4
!

!
3u + v
u 3v
fY
, < u, v < ,
4
4

using the assumed independence of X and Y . The exact form of fX and fY gives

!2

!2

1
1
1
3u + v
1
1 u 3v
fU,V (u, v) = exp
exp
2

4
4
4
2
2



1
1  2
2
2
2
=
exp
3u + 2 3 uv + v + u 2 3 uv + 3v
8
2 16



1
1
2
2
=
exp
4u + 4v
8
2 16




u2
u2
1
1
exp
= exp
24
24
2 2
2 2
provided that < u < , < v < . Hence, we immediately conclude
that fU,V (u, v) = fU (u) fV (v) and so U and V are independent random variables.
Furthermore, we recognize that both U and V have a N (0, 4) density. Together, this
implies that U |V = v N (0, 4).